2015
DOI: 10.5430/ijhe.v4n4p105
|View full text |Cite
|
Sign up to set email alerts
|

Using VineUp to Match Students with Alumni Industry Mentors in Engineering: A Pilot Study

Abstract: This pilot study evaluated users' perceptions of the effectiveness of the VineUp platform to match mentors from a large United States manufacturing firm and mechanical engineering students in an honors program at a small private university. Four mentor/mentee pairs were surveyed and interviewed at the end of the nine-month program. Although the VineUp platform was effective in matching mentor/mentee pairs, participants felt the process could have been done with an alternate method that was more cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Other studies also showed a positive effect from using an online tool to match mentor and student characteristics (Martin & Bok, 2015;Rees Lewis et al, 2015). In another study, mentors were not persuaded of the benefits of the specific online mentoring platform they were using but were in favor of a similar mentoring matching process through another site such as LinkedIn, Skype, or a university-created mentoring program (Halupa & Henry, 2015).…”
Section: Mentoring In-person Online or Blendedmentioning
confidence: 96%
See 3 more Smart Citations
“…Other studies also showed a positive effect from using an online tool to match mentor and student characteristics (Martin & Bok, 2015;Rees Lewis et al, 2015). In another study, mentors were not persuaded of the benefits of the specific online mentoring platform they were using but were in favor of a similar mentoring matching process through another site such as LinkedIn, Skype, or a university-created mentoring program (Halupa & Henry, 2015).…”
Section: Mentoring In-person Online or Blendedmentioning
confidence: 96%
“…These programs may have a formal mentoring selection process, specific guidance on how mentors and mentees should interact, and follow up at the end of the program. Structured programs can help lessen concerns for mentors and mentees as new partnerships begin because expectations are established based on the program outline (Ambrose & Williamson Ambrose, 2013;Halupa & Henry, 2015). Particularly when there may be racial or cultural differences, these structured programs such as featured in the Dahlvig (2010) study, could facilitate a positive meeting experience and as one study participant described, "force people to get uncomfortable" (p. 39).…”
Section: Mentoring Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…The research does not give specific suggestions for maximizing that personalized experience. Additional recommendations are needed regarding time and student development in the mentoring relationship, including short-and long-term goal-setting, which is cited by many as one of the most important functions of mentoring (Ambrose & Williamson Ambrose, 2013;Halupa & Henry, 2015;Houck, 2011).…”
Section: Themes From Researchmentioning
confidence: 99%